Nurul Maghfiroh Dampak Pernikahan Dini Terhadap Pola Pembelajaran Pendidikan Agama Islam Di Masyarakat Jatiurip Probolinggo: Dampak Pernikahan Dini Terhadap Pola Pembelajaran Pendidikan Agama Islam Di Masyarakat Jatiurip Probolinggo - Magfhiroh, Nurul (TABYIN: JURNAL PENDIDIKAN ISLAM, 2025)
This research aims to determine the impact of early marriage on Islamic religious education learning patterns in the Jatiurip Probolinggo community, as well as how parents who marry early educate their children. This research used interview techniques with 3 informants, namely Mr. Saiful Bakhri, Mrs. Farah, and Mrs. Riris. This research uses validity checking using the source triangulation method. The results of this research are the first impact of early marriage in the Jatiurip Probolinggo community, namely dropping out of school, lack of insight into Islamic religious education, decreased intelligence for children born in the Jatiurip Probolinggo community, the second result is about how to educate parents who marry early using The first 2 methods of education are taught with a democratic parenting style, the second with an authoritarian parenting style.